ال Dialectic Contrast in Contemporary Arabic - Al-Muhairi, Mariam Saeed Khalifa; Al-Ketbi, Dr. Mariam Saeed (Al-Adab Journal, 2020)
This study does not seek to investigate the dialect and its beauty, where specialist and non-specialist Arabic speaker all agree that classical Arabic has its own glamour that no other language has. However, it seeks to explore a linguistic phenomenon known as “dialectic contrast” which creates a semantic ambiguity, in order to be cautious from blinding the intended meaning, as it becomes misunderstood in our daily pragmatic communication. This study focuses on dialectic contrast phenomenon in contemporary Arabic dialects. It is divided into three domains; the first domain is concerned with manifesting the concept of dialectic contrast and the factors that led to its difference without tackling its branching and development, but rather explore the cause that illustrates the statement deviation of the Arabic speaker, which led to a difference that exists between the dialects and their placements among linguistic levels. The second domain, it tackles the phenomenon of language confusion, by expressing “language confusion” as a terminology and language, and distinguishing between it and similar terminologies, such as confusion, ambiguity, delusion, and mystery, as well as the relationship between confusion and dialect, and the rule which governs the confusion occurring in the dialect, and the proposed placements that create confusion on language levels, specifically on the lexical level, which is the subject of the study. As for the third domain, it observes some verbal instances that reveal the effect of the dialects variations in communication via examples from daily real life situations that led to lexical ambiguity, as it presents an overview and not an analysis